EFL students’ voices on English national examination in Indonesia - Yulnada Sari; Bambang Widi Pratolo; Dhei Klaudiya; Bella Nusa Bahari (Universitas Ahmad Dahlan)
This research examines the students’ voices on national examination of English subject using Computer-Based Test (CBT) in Indonesia. The research design in this study applies qualitative research. The participants of this research consist of seven graduated students from senior high school and they used CBT in their National English examination. The data was obtained through in-depth interview. Therefore, the finding of this research defines that most of the students agree with Computer-Based Test (CBT) as standardized of national examination especially in English subject in Indonesia. CBT has the positive contribution for the students, such as it is easy to access, flexible, simpler and more practical than PBT, and it is not time consuming. Besides, it motivates the students to learn English through technology and helps them answer the questions both in listening and reading sections easily. However, the students encounter some difficulties in CBT dealing with internal and external factors namely student’s anxiety, the background knowledge of the students, and lack of the school facilities, internet connection, and technical problems.